Pilkades as A Political Representation of Village Society in the Novel Desa Sajeroning Ombak - Sofia Nur Laeli; Edy Nugroho, Yusro; Ari Widihastuti, Rahma (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2025)
Literature and politics are an interesting combination. Not only as entertainment, but literature is also a means of critiquing societal issues. Desa Sajeroning Ombak is one of Sela Istighfari's novels that describes the process of community politics in the village and the conflicts that arise during its implementation. Therefore, this study aims to identify (1) the forms of political conflict during village elections, and (2) the factors causing political conflict during village elections in the novel Desa Sajeroning Ombak. This study employs a mimetic approach and utilizes Ian Watt's literary sociology theory as its theoretical framework. The data collected includes characters, plot, and setting sourced from the novel Desa Sajeroning Ombak by Sela Istighfari. The analysis was conducted using hermeneutic techniques. The findings show that the village head election process in the novel Desa Sajeroning Ombak involves three forms of conflict: (1) conflict between individuals, between Pak Surya and Haidar; (2) conflict between groups, between traditional fishermen and industrial workers; and (3) conflict between the village government and the village community. In addition, the factors causing the conflicts are (1) competition, (2) differences in interests, (3) loss of public trust, and (4) natural disasters. In the implementation of the village head election, the conflicts that arise cause divisions within the community.